Perceived Indoor Air Quality and Sick Building Syndrome among Work-From-Home Workers Using Geospatial Approach - Aziz, Norsaffarina; Adman, Mohammad Adam; Suhaimi, Nurud Suria; Misbari, Syarifuddin; Lim, Fang Lee; Khan, Md Mobarak Hossain; Abd Aziz, Azrina (International Journal of Integrated Engineering, 2025)
This study aims to assess the associations between perceived indoor air quality (PIAQ) and several risk factors for sick building syndrome (SBS) among work-from-home (WFH) workers through appropriate statistical analyses. Using a geospatial approach, it also aims to identify the spatial correlation between PIAQ and SBS. The study was conducted among 131 WFH workers in Kuantan through a questionnaire survey. Multiple logistic regression was used to analyse the associations between the risk factors of PIAQ and SBS symptoms. The significant factors associated with the SBS symptoms were further analysed using a geospatial approach. The study found the prevalence of SBS by WFH workers in Kuantan was 75.6%. The most prevalent symptom reported was difficulty concentrating (42.7%), while nausea (9.2%) was the least prevalent symptom. There was no significant difference between gender and SBS symptoms. Findings showed associations between SBS symptoms and PIAQ climate factors such as draught 3.28 (1.01-10.59) and dust 2.82 (1.01-7.87). The geospatial approach of this study illustrates a visual mapping of the hotspot of SBS symptoms and the correlation between the risk factors and SBS. These findings underscore the importance of addressing IAQ issues among WFH workers to mitigate the occurrence of SBS symptoms.